- Serum Cytokines as Potential Biomarkers for Diagnosis and Monitoring of Sleep Disorders: A Cross-Sectional and Longitudinal Study: Serum levels of IL-6, TNF-α, IL-1β, IL-10, and CRP - Yao, Yongliang; Pan, Yifan; Yan, Lei; Zheng, Chaoan (Journal of Medical Biochemistry, 2026)
Background: Sleep disorders, particularly Obstructive Sleep Apnea (OSA) and Insomnia Disorder (ID), are associated with systemic inflammation. However, the diagnostic and monitoring utility of specific cytokine profiles remains unclear. Objective: To identify distinct serum cytokine signatures in OSA and ID compared to healthy controls (HC) at baseline and to evaluate longitudinal changes in these biomarkers following standard treatment. Methods: In this pilot study, 75 cases (25 OSA, 25 ID, 25 HC) were enrolled. Serum levels of IL-6, TNF-α, IL-1β, IL-10, and CRP were measured at baseline using multiplex immunoassay. All patients underwent polysomnography and clinical assessment. The OSA and ID cohorts were re-evaluated after 3 months of treatment (CPAP for OSA, CBT-I for ID) with repeat cytokine analysis. Results: At baseline, the OSA group showed significantly elevated levels of IL-6 (p<0.001), TNF-α (p=0.003), and CRP (p<0.001) compared to HC. The ID group had elevated IL-6 (p=0.01) and IL-1β (p=0.02) but not CRP. A combined panel of IL-6, TNF-α, and IL-1β differentiated OSA from ID with an AUC of 0.87 (95% CI: 0.78-0.96). Longitudinally, CPAP therapy in adherent patients (>4 hrs/night) led to a significant reduction in IL-6 (p=0.004) and CRP (p=0.008), correlating with apnea-hypopnea index (AHI) improvement (r=0.65, p=0.002). CBT-I in ID led to a reduction in IL-1β (p=0.03), which correlated with improved sleep efficiency (r=-0.52, p=0.02). Conclusion: This pilot study identifies disorder-specific inflammatory profiles in OSA and ID. Serum IL-6 and CRP are promising biomarkers for OSA severity and treatment response, while IL-1β may be salient to insomnia pathophysiology. These findings support the role of cytokines as complementary objective tools for diagnosis and monitoring in sleep medicine.